2010
DOI: 10.1681/asn.2009040451
|View full text |Cite
|
Sign up to set email alerts
|

Cholecalciferol Supplementation Alters Calcitriol-Responsive Monocyte Proteins and Decreases Inflammatory Cytokines in ESRD

Abstract: In vitro, monocyte 1␣-hydroxylase converts 25-hydroxyvitamin D [25(OH)D] to 1,25-dihydroxyvitamin D to regulate local innate immune responses, but whether 25(OH)D repletion affects vitamin D-responsive monocyte pathways in vivo is unknown. Here, we identified seven patients who had 25(OH)D insufficiency and were undergoing long-term hemodialysis and assessed changes after cholecalciferol and paricalcitol therapies in both vitamin D-responsive proteins in circulating monocytes and serum levels of inflammatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
4
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(127 citation statements)
references
References 61 publications
4
115
4
4
Order By: Relevance
“…Although active vitamin D therapy associated with a significant survival benefit in observational studies, 85 there is growing interest in treating patients with inactive vitamin D precursors to decrease or obviate altogether the requirement for exogenous active vitamin D. 86 The basis for this approach is that peripheral activation of vitamin D precursors by extrarenal cells that express CYP27B1 (1-␣-hydroxylase) will generate adequate amounts of calcitriol locally 87 ; however, few studies have examined the regulation of peripheral CYP27B1 and whether it functions normally in CKD in the setting of very high FGF23 levels. In a recent report, 88 cholecalciferol repletion in dialysis patients induced calcitriol-dependent protein expression in monocytes, suggesting intact peripheral CYP27B1, but the effect could have been mediated by the increase in systemic (from the kidney) calcitriol levels that were observed. Determining whether a markedly increased FGF23 level inhibits peripheral CYP27B1 will strengthen the physiologic basis for designing optimal vitamin D regimens in CKD.…”
Section: How Do Fgf23 Levels Differ In Specific Ckd Subpopulations?mentioning
confidence: 94%
“…Although active vitamin D therapy associated with a significant survival benefit in observational studies, 85 there is growing interest in treating patients with inactive vitamin D precursors to decrease or obviate altogether the requirement for exogenous active vitamin D. 86 The basis for this approach is that peripheral activation of vitamin D precursors by extrarenal cells that express CYP27B1 (1-␣-hydroxylase) will generate adequate amounts of calcitriol locally 87 ; however, few studies have examined the regulation of peripheral CYP27B1 and whether it functions normally in CKD in the setting of very high FGF23 levels. In a recent report, 88 cholecalciferol repletion in dialysis patients induced calcitriol-dependent protein expression in monocytes, suggesting intact peripheral CYP27B1, but the effect could have been mediated by the increase in systemic (from the kidney) calcitriol levels that were observed. Determining whether a markedly increased FGF23 level inhibits peripheral CYP27B1 will strengthen the physiologic basis for designing optimal vitamin D regimens in CKD.…”
Section: How Do Fgf23 Levels Differ In Specific Ckd Subpopulations?mentioning
confidence: 94%
“…IL-6 and MCP-1 are important inflammatory cytokines. In addition, it has been reported that low levels of 25(OH)D 3 and VD receptor (VDR) may be involved in the genesis of the complications that occur in DM [14]. This study demonstrated that Pit-1 expression is in positive correlation with MCP-1 concentration suggesting that Pit-1 is associated with monocytes dysfunction involved in inflammation and pathogenesis of DNU.…”
Section: Discussionmentioning
confidence: 64%
“…Besides, any reduction in UACR must also be interpreted in the context of its biological variation in patients with diabetes, which is estimated at 61%. 2 Second, the mean concentration of vitamin D in the patients included (40 nmol/L) is far below the current recommendations 3,4 and refl ects a severe defi ciency. Subgroup analysis according to the 25-hydroxyvitamin D concentration would be of interest.…”
Section: Paricalcitol For Reduction Of Albuminuria In Diabetesmentioning
confidence: 85%
“…Since observational studies have shown that higher concentrations correlate with mortality in diabetic populations with and without renal disease, 2,3 their value might be of extreme importance.…”
Section: Paricalcitol For Reduction Of Albuminuria In Diabetesmentioning
confidence: 99%